2009
DOI: 10.1042/cs20080196
|View full text |Cite
|
Sign up to set email alerts
|

Role of TNF-α in vascular dysfunction

Abstract: Healthy vascular function is primarily regulated by several factors including EDRF (endothelium-dependent relaxing factor), EDCF (endothelium-dependent contracting factor) and EDHF (endothelium-dependent hyperpolarizing factor). Vascular dysfunction or injury induced by aging, smoking, inflammation, trauma, hyperlipidaemia and hyperglycaemia are among a myriad of risk factors that may contribute to the pathogenesis of many cardiovascular diseases, such as hypertension, diabetes and atherosclerosis. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
448
1
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 590 publications
(486 citation statements)
references
References 111 publications
(122 reference statements)
13
448
1
24
Order By: Relevance
“…Several studies also suggest that smoking induces production of inflammatory cytokines such as TNFand CRP 26) that are risk factors for atherosclerosis. Increased levels of TNF-and C-reactive protein (CRP) induce the production of ROS (reactive oxygen species), resulting in endothelial dysfunction under many pathophysiological conditions 27,28) . TNF-, whose produced is increased in an insulin-resistant state, also dose-dependently suppresses the expression of adiponectin in adipocytes by suppressing promoter activity 29) .…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Several studies also suggest that smoking induces production of inflammatory cytokines such as TNFand CRP 26) that are risk factors for atherosclerosis. Increased levels of TNF-and C-reactive protein (CRP) induce the production of ROS (reactive oxygen species), resulting in endothelial dysfunction under many pathophysiological conditions 27,28) . TNF-, whose produced is increased in an insulin-resistant state, also dose-dependently suppresses the expression of adiponectin in adipocytes by suppressing promoter activity 29) .…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In addition to our own previous findings, (40) others have also shown that TNF-α down-regulates eNOS and/or reduces NO production in various models of endothelial cells. (41)(42)(43) Furthermore, the induction of ROS generation by TNF-alpha, (44,45) as well as its pro-apoptotic effects (47,47) have extensively been described.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, что ЭЖ продуцирует про-воспалительные цитокины ИЛ-1, ИЛ-6 и ФНО-, а так-же хемокин МСР-1 (monocyticchemotactic protein-1), ока-зывая патологическое воздействие на сосудистое русло. Сужение сосудов, индуцированное ФНО-, свя-зано с увеличением производства ангиотензина II и эн-дотелина-1 [47]. Кроме того, TNF- уменьшает секре-цию адипонектина и стимулирует выработку других про-воспалительных веществ, тем самым способствуя поддержанию хронического воспалительного процес-са в жировой ткани.…”
Section: выпуск 1 (61) 2017unclassified